Tinjauan Biopsikologi pada Kasus Disleksia Anak yang Dilahirkan oleh Ibu yang Mengalami Stress Psikis Berat - Ambar Sulianti; Maulana Basri; Gulam Gumelar (Jurnal Psikologi Integratif, 2016)
Psychological stress is the body's reaction to psychosocial stressors/mental stress. Stress explains various unfavorable stimulus intensity i.e. disproportionate responses to physiological, behavioral, and subjective to stress. Psychological stress among pregnant women affects the situation of pregnant women and the fetus. This study aims to analyze biopsychological review in the case of dyslexic child born from mother with severe psychological stress.This study is a qualitative study through survey techniques, observation, and interviews on the subjectof research. The research subject is a 13-year-old dyslexic child. While in the uterus, his mother experienced severe psychological stress due to become a kidnap victim. The results showed the dyslexia on the research subject due to the failure of his mother in managing severe stress experienced while having pregnancy. This condition impacted to low fetus nutrition during the womb phase and inadequate mother’s time to rest so that activated the mechanism of CRH, epinephrine, and norepinephrine that cause prenatal birth and low birth weight. Families’ supports, especially parent caused the self confidence and ability of social interaction on the subject